Up-Regulation of miR-9-5p Inhibits Hypoxia-Ischemia Brain Damage Through the DDIT4-Mediated Autophagy Pathways in Neonatal Mice - Gai C; Xing X; Song Y; Zhao Y; Jiang Z; Cheng Y; Xiao Y; Wang Z (Dove Medical Press, 2023)
Chengcheng Gai,1,* Xiaohui Xing,1,2,* Yan Song,1 Yijing Zhao,1 Zige Jiang,1 Yahong Cheng,1 Yilei Xiao,2,3 Zhen Wang1,4 1Department of Physiology, School of Basic Medical Sciences, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, 250012, People's Republic of China; 2Department of Neurosurgery, Liaocheng People's Hospital, Liaocheng, Shandong, 252000, People's Republic of China; 3Liaocheng Neuroscience Laboratory, Liaocheng People's Hospital, Liaocheng, Shandong, 252000, People's Republic of China; 4Key Laboratory of Birth Regulation and Control Technology of National Health Commission of China, Maternal and Child Health Care Hospital of Shandong Province Affiliated to Qingdao University, Jinan, 250014, People's Republic of China*These authors contributed equally to this workCorrespondence: Yilei Xiao, Department of Neurosurgery, Liaocheng People's Hospital, Liaocheng, Shandong, 252000, People's Republic of China, Email yileixiao@163.com Zhen Wang, Department of Physiology, School of Basic Medical Sciences, Cheeloo College of Medicine, Shandong University, 44 Wenhua Xi Road, Jinan, 250012, Shandong, People's Republic of China, Email wangzhen@sdu.edu.cnIntroduction: Hypoxia-ischemia (HI) remains the leading cause of cerebral palsy and long-term neurological sequelae in infants. Despite intensive research and many therapeutic approaches, there are limited neuroprotective strategies against HI insults. Herein, we reported that HI insult significantly down-regulated microRNA-9-5p (miR-9-5p) level in the ipsilateral cortex of neonatal mice.Methods: The biological function and expression patterns of protein in the ischemic hemispheres were evaluated by qRT-PCR, Western Blotting analysis, Immunofluorescence and Immunohistochemistry. Open field test and Y-maze test were applied to detect locomotor activity and exploratory behavior and working memory.Results: Overexpression of miR-9-5p effectively alleviated brain injury and improved neurological behaviors following HI insult, accompanying with suppressed neuroinflammation and apoptosis. MiR-9-5p directly bound to the 3' untranslated region of DNA damage-inducible transcript 4 (DDIT4) and negatively regulated its expression. Furthermore, miR-9-5p mimics treatment down-regulated light chain 3 II/light chain 3 I (LC3 II/LC3 I) ratio and Beclin-1 expression and decreased LC3B accumulation in the ipsilateral cortex. Further analysis showed that DDIT4 knockdown conspicuously inhibited the HI-up-regulated LC3 II/ LC3 I ratio and Beclin-1 expression, associating with attenuated brain damage.Conclusion: The study indicates that miR-9-5p-mediated HI injury is regulated by DDIT4-mediated autophagy pathway and up-regulation of miR-9-5p level may provide a potential therapeutic effect on HI brain damage.Keywords: hypoxia-ischemia, HI, miR-9-5p, DNA damage-inducible transcript 4, (DDIT4), autophagy